2021
DOI: 10.3390/v13091675
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Eosinophil Counts in Recovered and Deceased COVID-19 Patients over the Course of the Disease

Abstract: Knowledge about the immune responses against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, particularly regarding the function of eosinophils, has been steadily emerging recently. There exists controversy regarding the implications of eosinophils in the coronavirus disease 2019 (COVID-19)’s pathology. We report a retrospective cohort study including the comparison of leukocyte counts in COVID-19 patients, considering the outcomes of recovery (n = 59) and death (n = 60). Among the diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 54 publications
(88 reference statements)
5
24
0
1
Order By: Relevance
“…Previous study demonstrated that severe patients tend to have lower lymphocytes counts, higher leukocytes counts and neutrophil–lymphocyte-ratio (NLR), as well as lymphopenia has been reported as a predictor of prognosis in COVID-19 patients [ 9 , 14 , 15 ]. Our data also revealed that the initial counts of lymphocytes, eosinophils, and basophils of COVID-19 patients were much lower in non-survivors compared with the counts of above indices in survivors, which was consistent with conclusion of other studies [ 11 , 12 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Previous study demonstrated that severe patients tend to have lower lymphocytes counts, higher leukocytes counts and neutrophil–lymphocyte-ratio (NLR), as well as lymphopenia has been reported as a predictor of prognosis in COVID-19 patients [ 9 , 14 , 15 ]. Our data also revealed that the initial counts of lymphocytes, eosinophils, and basophils of COVID-19 patients were much lower in non-survivors compared with the counts of above indices in survivors, which was consistent with conclusion of other studies [ 11 , 12 ].…”
Section: Discussionsupporting
confidence: 93%
“…Several cohort studies have reported that lymphopenia can predict prognosis in COVID-19 patients [ 9 , 10 ]. In addition, a few studies found that the eosinopenia was also associated with poor prognostic features [ 11 , 12 ]. Thus, the differentiation of peripheral white blood cells may indicate the immunologic impairment at the early stage of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, our results showed a significant association between low eosinophil counts and COVID-19 severe outcomes. It was suggested that eosinophils could play beneficial functions in COVID-19 patients, probably contributing by controlling the exacerbated inflammation induced by neutrophils ( Cortes-Vieyra et al, 2021 ). Even if the role of eosinophils in inflammation remains controversial, recent evidence suggested that different eosinophils subpopulations in the same tissue could differentially modulate inflammatory responses ( Kanda et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…We also found that children with asthma presenting with COVID‐19 had lower eosinophil counts and fewer atopic comorbidities than asthma controls. Eosinopenia has been associated with worse outcomes and mortality in adult COVID‐19 36,37 . Eosinophils play an important role in the immune response to respiratory viruses; atopic patients with higher eosinophil counts may be somewhat “protected” from SARS‐CoV‐2 infection, 38 and A+C cases with relatively lower counts may have thus been more susceptible.…”
Section: Discussionmentioning
confidence: 99%